Investigating the Role of Emotional Intelligence and Role Conflict on Job Burnout among Special Education Teachers - Olatunji, Olabimpe Ajoke; Idemudia, Erhabor Sunday; Owoseni, Omosolape Olakitan (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The need to take appropriate care of children with disabilities by the relevant stakeholders as the world moves into the post-COVID era has become imperative. Hence, this work investigated how family-to-work, work-to-family conflicts, and emotional intelligence influenced the four dimensions of job burnout (enthusiasm towards the job, psychological exhaustion, indolence, and guilt) among teachers administering children with disabilities. This was assessed using a cross-sectional online survey design of 276 special education teachers (female = 159; mean age = 32.5, SD = 10.1) from the Nigerian population of teachers. Data were collected using structured psychological tests, including the Work and Family Conflict Scale (WFCS), Emotional Intelligence Scale, and Job Burnout Scale. Results indicated that emotional intelligence predicted all the dimensions of job burnout in teachers except psychological exhaustion. The independent variables failed to predict psychological exhaustion; however, family-to-work conflict independently predicted indolence. Furthermore, the results revealed no gender difference in all four dimensions of job burnout. Based on these findings, it was recommended that an intervention strategy targeting the promotion of emotional intelligence and adequate provision of modern facilities to be used to assist teachers in their special skills delivery.